The Effect of Adding Zinc on the Mechanical and Microscopic Properties of the Al-Ni Composite Prepared using Powder Technology - Hammoud, Moayed Abdel Razzaq Taha; Salman, Dr. Ibrahim Khalaf (Migration Letters, 2023)
Aluminum and its compounds are important materials due to their availability and properties, which has enhanced their applications in many fields. This study aims to detect the effect of strengthening with zinc particles on the mechanical and microscopic properties and adding it to the composite (Al_Ni). The composite (aluminum_nickel_zinc) is prepared by powder metallurgy with the volumetric proportions of aluminum ( 97, 94, 91, 88, 85%) and nickel at a fixed percentage (3%) with zinc reinforcement at volumetric percentages of (12, 9, 6, 3, 0)%. The metal powders are grounded for an hour and then pressed at a pressure of 6 tons for a minute for all samples in order to achieve good harmony between its components, Then, the samples are annealed at a temperature of 600 °C for a period of two hours. After that, the mechanical properties (hardness, compressive strength) are studied. The results show an increase in both Vickers hardness and compressive strength values with increasing zinc particle content before and after sintering. The morphological (microscopic) properties show dispersion and dissolution of zinc particles in aluminum and the replacement of dark phases with bright ones with increasing zinc concentration.